Isolation and Identification of Pantoea agglomerans from Open Heart Operations Unit of Marjan Hospital in Hilla City - Enas R . Al-Kidsawey1, Kawther H. Mhdi1, Mohammed A. Al kaif1 (Indian Journal of Forensic Medicine & Toxicology, 2020)
The nosocomial infection of Pantoea agglomerans has become an important cause of many systemic infections in humans, and considered of present study was to isolate and identify this pathogen from open heart operation unit of Marjan hospitals in Hilla city during a period from April to September 2018, (19) isolates of Pantoea agglomerans. Was isolated from (150) swaps which were collected from the environmental of open heart operation unit. 8/30 isolates from system, 3/35 from bed, 3/25 from earth , 3/35 from door and 2/25 from nurse hands isolated identification of microbes were done according on the morphological, cultural ,microscopically characterization and list of biochemical test. To emphasize the identification of Pantoea agglomerans. We used the API20 technique biochemical strips ( biomerieux SA/marc y-1 Etoile France).The antimicrobial susceptibility pattern of the isolates was studied using different types of antibiotics. The microbes showed resistance to the routinely used antibiotics.